Foreign currency exposure and the financial channel of exchange rates - Pablo Anaya (European Central Bank (ECB), 2022)
Exchange rate movements affect the economy through changes in net exports, i.e. the trade channel, and through valuation changes in assets and liabilities denominated in foreign currencies, i.e. the financial channel. In this paper, I investigate the macroeconomic and financial effects of U.S. dollar (USD) exchange rate fluctuations in small open economies. Specifically, I examine how the financial channel affects the overall impact of exchange rate fluctuations and assess to what extent foreign currency exposure determines the financial channel's strength. My empirical analysis indicates that, if foreign currency exposure is high, an appreciation of the domestic currency against the USD is expansionary and loosens financial conditions, which is consistent with the financial channel of exchange rates. Moreover, I estimate a small open economy New Keynesian model, in which a fraction of the domestic banks' liabilities is denominated in USD. In line with the empirical results, the model shows that an appreciation against the USD can be expansionary depending on the strength of the financial channel, which is linked to the level of foreign currency exposure. Finally, the model indicates that the financial channel amplifies the effects of foreign monetary policy shocks.
Keywords: E44; F31; F41; 330; Exchange rates; financial and trade channels; local projections - instrumental variable; open economy DSGE model